On the measurement of the social benefits of a custom union - Mantel, Rolf R. (2001)
It is the purpose of the presente paper to present a procedure to estimate the benefits of economic integration from the point of view of the members of the union, separating these benefits from those obtained from a more rational commercial policy, in the spirit of a previous essay (Mantel and Martirena-Mantel, 1973). (Párrafo extraído del texto a modo de resumen)